DEVELOPING SUPPLEMENTARY INTERACTIVE MEDIA TO IMPROVE STUDENTS’ READING COMPREHENSION SKILL OF RECOUNT: HISTORICAL TEXT IN TUMBUH KEMBANG SENIOR HIGH SCHOOL CANDIPURO LUMAJANG - Rifqo Insyiani Zanah (Language-Edu, 2021)
With the growth of the technology, this study is aimed to develop a supplementary media in the form of interactive media that can help students in improving their reading comprehension skill of “Recount:Historical text” and produce a guideline to help the students using the media.  This research adapts two models of research and development from Latief (2017) and ADDIE by Taylor (2004). The final product is in the form of interactive media that can be played in android devices and PC/laptop. The media was the result of need analysis conducted by the researcher. The media was assesed by the expert using a questionnaire and tried out to the students. Then being analysed using SPSS. The result of the questionnaires by the expert for the media was 94%. Meanwhile, in mean pretest and  mean posttest of the try out, there is a difference in the amount of 30,55 which that mean posttest is bigger than mean pretests.. It can be concluded that there is significance difference in students’ reading comprehension, before and after they use the interactive media. The above explanation strengthens that the interactive media give a positive attribute in the process of learning.